Konstruksi Pendidikan Tauhid pada Pengajian Sholawat Burdah Pondok Pesantren Maulana Rumi Timbulharjo Sewon Bantul Yogyakarta - Isna Wahyu Hidayati (NALAR, 2021)
This study intends to understand the construction of the tawheed education in the Burdah recitation at Pondok Pesantren Maulana Rumi Timbulharjo Sewon Bantul. This is a field research and uses the social construction theory of Berger L. Peter and Thomas Luckman. It takes a qualitative approach. The data is collected by observation, interviews and documentation. The result concludes that the construction of tawheed education in the Burdah recitation is through three processes. First is the externalization process, because the knowledge of tawheed is given repeteadly both in Saturday night and Sunday Wage night gatherings. Second is the objectification, because the tawheed education becomes the truth and logical understanding, and it reminds us that everything originates from the Divine. Third is the internalization, because it is able to give motivation and spiritual peace to the audience and it eventually forms a noble personality.Keywords: Construction, Tawheed Education, Burdah Recitation